Pepe leaf extract (gymnema sylvestre) to reduce blood glucose levels in pregnant women with a history of gestational diabetes mellitus - Retno Dewi Prisusanti; Santy Irene Putri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Gestational diabetes mellitus (GDM) is a glucose intolerance disorder that appears during pregnancy and has the potential to cause complications in both mother and fetus. The use of pharmacological therapies such as insulin is often constrained by safety limitations in pregnant women, so a safe and effective adjuvant alternative is needed. Gymnema sylvestre (pepe leaf) is known to have hypoglycemic effects through the mechanism of inhibiting glucose absorption, stimulating β pancreatic cell function, and increasing peripheral glucose utilization. Purpose: To evaluate the effectiveness of pepe leaf extract (gymnema sylvestre) in reducing blood glucose levels in pregnant women with a history of gestational diabetes mellitus. Method: A quasi-experiment with a pretest-posttest control group design. The study took place from August 2025 in Community Health Center Bumiaji, Batu Malang. The independent variables studied were effectiveness of pepe leaf extract (Gymnema sylvestre), while the dependent variable was blood glucose levels. Using purposive sampling and lameshow formula 60 participants were selected devided into two group, who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondents characteristics, followed by bivariate analysis using paired t-test. Results: Before the intervention, the mean fasting blood glucose (FBG) levels were 129.1±6.9 mg/dL in the treatment group and 124.6±4.7 mg/dL in the control group. After the intervention, mean FBG decreased to 117.5±6.2 mg/dL in the treatment group and 113.0±5.4 mg/dL in the control group. The post-intervention difference between groups was statistically significant (p<0.001), demonstrating a significant effect of the intervention on reducing fasting blood glucose levels. Conclusion: Showed that the intervention provided was effective in reducing fasting blood glucose (GDP) levels in pregnant women with a history of gestational diabetes.